2015
DOI: 10.4236/ce.2015.614151
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Primary School Students’ 3D Geometrical Thinking within a Dynamic Transformation Context

Abstract: This study examines children's thinking about geometrical solids through an investigation of dynamic transformations employed by young children making mental transformations of an orthogonal parallelepiped. The focus of the study is on the investigation of the role that a dynamic environment could play in the development of children's geometrical thinking concerning geometrical solids and their properties. Twenty 6th grade children, who had previously worked with dynamic transformations of physical models of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…This is because the ability of technology is easy to manipulate and manage, making it easier for students to understand a concept compared to conventional learning [50]. [41] as well as Škrbec and Čadež [40] used varied materials and concrete experiences in developing students' geometric thinking. However, Markopoulos, et al [41] found that not all students achieved an advanced level of thinking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because the ability of technology is easy to manipulate and manage, making it easier for students to understand a concept compared to conventional learning [50]. [41] as well as Škrbec and Čadež [40] used varied materials and concrete experiences in developing students' geometric thinking. However, Markopoulos, et al [41] found that not all students achieved an advanced level of thinking.…”
Section: Methodsmentioning
confidence: 99%
“…[41] as well as Škrbec and Čadež [40] used varied materials and concrete experiences in developing students' geometric thinking. However, Markopoulos, et al [41] found that not all students achieved an advanced level of thinking. Also, according to the findings of Škrbec and Čadež [40], there was no substantial difference between the two groups in terms of the level reached, such as the number of points at level 0, level 1.5, and level 2.…”
Section: Methodsmentioning
confidence: 99%
“…With these devices, frontiers between 3D objects and representations of these 3D objects are pushed (Lowrie, 2002). Several authors, for example Gutié rrez (1996) or Markopoulos et al (2015), suggest that those types of representations could be pertinent for learning 3D geometry. A survey about teaching practice in France and French-speaking Belgium shows that this type of environments is not widely used even if some teachers used this materiel from the first years of school (Seha et al, 2023).…”
Section: Area Descriptionsmentioning
confidence: 99%
“…Meanwhile, [15] studied 3D geometric thinking skills in children after participating in the 3D program in Early Childhood (3DinEC). Furthermore, [16] investigated this process in children using the Dynamic Transformation Context program and [17] tested the effect of AR on students' 3D geometric thinking skills during learning.…”
Section: Introductionmentioning
confidence: 99%